Prospective Evaluation of Maternal Sleep Position Through 30 Weeks of Gestation and Adverse Pregnancy Outcomes. Issue 3 (March 2020) - Silver, Robert M.; Hunter, Shannon; Reddy, Uma M.; Facco, Francesca; Gibbins, Karen J.; Grobman, William A.; Mercer, Brian M.; Haas, David M.; Simhan, Hyagriv N.; Parry, Samuel; Wapner, Ronald J.; Louis, Judette; et al.
Abstract : (Abstracted from Obstet Gynecol 2019;134:667–676) Maternal sleep position has been associated with adverse pregnancy outcomes including fetal growth restriction and stillbirth. Despite prior data suggesting a relation between supine sleep position and adverse pregnancy outcomes, there remains uncertainty in regard to the validity of these findings, due to the potential for recall bias.